2020
DOI: 10.1136/bmjopen-2019-034524
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of deep learning methods for predicting under-five mortality in 34 low-income and middle-income countries

Abstract: ObjectivesTo explore the efficacy of machine learning (ML) techniques in predicting under-five mortality (U5M) in low-income and middle-income countries (LMICs) and to identify significant predictors of U5M.DesignThis is a cross-sectional, proof-of-concept study.Settings and participantsWe analysed data from the Demographic and Health Survey. The data were drawn from 34 LMICs, comprising a total of n=1 520 018 children drawn from 956 995 unique households.Primary and secondary outcome measuresThe primary outco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…2 3 25 52-54 Ezeh et al, 54 found that mother's education level and household wealth influenced child survival in Nigeria. A similar study by Adegbosin et al, 25 that used deep learning techniques in predicting U5MR in low-inome and middle-income countries, ranked mother's education and household wealth index among the most critical predictors of U5MR. The same study found that deep learning techniques are superior in predicting child survival, and a similar conclusion has been arrived at in other similar studies.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…2 3 25 52-54 Ezeh et al, 54 found that mother's education level and household wealth influenced child survival in Nigeria. A similar study by Adegbosin et al, 25 that used deep learning techniques in predicting U5MR in low-inome and middle-income countries, ranked mother's education and household wealth index among the most critical predictors of U5MR. The same study found that deep learning techniques are superior in predicting child survival, and a similar conclusion has been arrived at in other similar studies.…”
Section: Discussionmentioning
confidence: 77%
“…The survey uses a two-stage cluster sampling. 25 More information about the sampling design, data collection and processing details are described on the DHS programme website. The datasets are available on request from the DHS programme.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations